2019
DOI: 10.1001/jamanetworkopen.2019.1350
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Rare Coding Mutations With Alzheimer Disease and Other Dementias Among Adults of European Ancestry

Abstract: Key Points Question Can rare genetic variants for Alzheimer disease be identified using nonstatistical approaches? Findings In this genetic association study, variants with high functional effect were observed in participants with Alzheimer disease but not in controls in NOTCH3 , a gene previously associated with cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 75 publications
1
60
0
Order By: Relevance
“…Of genes with SLPs above 3, a number have previously been implicated by sequencing studies, consisting of TREM2 , ABCA7 , SORL1 , and PSEN1 (Blue et al., ; Guerreiro et al., ; Kim, ; Patel et al., ; Raghavan et al., ). Many of the others did not seem likely to have any plausible role in AD susceptibility but there were some exceptions that we list here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of genes with SLPs above 3, a number have previously been implicated by sequencing studies, consisting of TREM2 , ABCA7 , SORL1 , and PSEN1 (Blue et al., ; Guerreiro et al., ; Kim, ; Patel et al., ; Raghavan et al., ). Many of the others did not seem likely to have any plausible role in AD susceptibility but there were some exceptions that we list here.…”
Section: Resultsmentioning
confidence: 99%
“…Using gene‐based analyses in the ADSP case‐control sample, TREM2 was significant at p = 1.8 × 10 −11 and APOE was significant at p = 0.0069, while ARSA , CSF1R , PSEN1 , and MAPT were less strongly implicated although were still significant at p < 0.05. In another study, 95 dementia‐associated genes were examined and it was reported that overall there was an excess of deleterious rare coding variants (Patel et al., ). Additionally, 10 cases and no controls carried rs149307620, a missense variant in NOTCH3 , and four cases and no controls carried rs104894002, a high‐impact variant in TREM2 , which in homozygous form causes Nasu–Hakola disease, which is a rare presenile dementia associated with recurrent bone fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a less aggressive progression, SAD shares the major characteristics of FAD, including Aβ plaque deposition and NFT pathology, and accounts for the vast majority (>95%) of all AD cases [28]. While no SAD-causative mutations have been found, a considerable number of genetic loci that increase or decrease the risk for developing SAD have now been reported [29][30][31][32][33][34]. The first identified was the APOE locus, encoding apolipoprotein E (APOE) [35].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Of genes with SLPs above 3, a number have previously been implicated by sequencing studies, consisting of TREM2, ABCA7, SORL1 and PSEN1 (Blue et al, 2018;Guerreiro et al, 2013;Kim, 2018;Patel et al, 2019;Raghavan et al, 2018). PIK3R1 codes for a key component of the PI3K/Akt/GSK-3β signalling pathway and in neuronally differentiated PC12 cells activation of this pathway is neuroprotective against Aβ25-35-induced apoptosis and tau hyperphosphorylation (Cheng et al, 2018).…”
Section: Resultsmentioning
confidence: 99%